The Effect of Interpersonal Communication, Emotional Intelligence, Supervision and Motivation of Achievement in Caring Behavior in Nursing - Abdurrahman Abdurrahman (Journal of Global Pharma Technology, 2020)
Background: The application of caring behavior based on knowledge of attitudes and professional behavior is important in nursing services. Nursing students who are carrying out professional education in hospitals must be able to understand and apply caring behavior in providing nursing care to patients. This study analyzes the effects of interpersonal communication, emotional intelligence, supervision, and achievement motivation on the caring behavior of nurses students in applying nursing care. Methods: Quantitative research with a path analysis approach. Sampling used a simple random sampling technique as many as 271 respondents from 871 populations. Data were collected using a developmental questionnaire. Results: interpersonal communication (p=0.385), emotional intelligence (p=0.134), clinical supervision  (p=0.286), achievement motivation (p=0.119) had a positive effect on caring behavior. Conclusion: Increasing interpersonal communication, emotional intelligence, clinical supervision, and achievement motivation can improve caring behavior.Keywords: Achievement motivation, Caring behavior, Emotional intelligence, Interpersonal communication, Supervision.